Sustainable management of mountain forests in the Czech Republic - S. Vacek; V. Balcar (Journal of Forest Science, 2004)
Forest management in the Czech Republic (CR) was not shaped in the environment of natural forests but in the territory that was influenced by unregulated felling and animal grazing for a long time. Hence the fear for sustainable and balanced benefits from forests endangered by long-term uncontrolled exploitation was legitimate. Almost after three centuries of application of the sustainability principle, forests are considered not only as a source of renewable wood raw material but also as a tool of the environment formation. Mountain forests are an important landscape component of this country. They are an object of specific importance from the aspect of natural environment conservation, stabilization of natural processes and general landscape homeostasis. In addition, they fulfil a number of production and non-production functions. Cardinal elements of sustainable forest management in the CR conditions are as follows: management of the forest as an ecosystem, i.e. transition from exclusive care of forest tree species and their stands to care of the whole forest ecosystems; restructuring (conversion, reconstruction) of damaged and declining forests; optimum (species, genetic, spatial, age) structure of forest ecosystems differentiated according to site conditions and management targets; differentiated transition from general management to group or individual methods; utilization and support of spontaneous processes such as natural regeneration, competition and other principles of self-regulation. The above cardinal elements of sustainable forest management are applicable to forests of the CR in general, but their importance considerably increases in mountain forests where many species survive on the margin of subsistence. Moreover, mountain forests of CR have been heavily destroyed by anthropogenic factors, especially air-pollution ecological stresses, during the last three or four decades.